PENGARUH METODE PEMBELAJARAN DISKUSI DAN SNOWBALL TROWING TERHADAP PENINGKATAN MOTIVASI BELAJAR IPS - Soleman Nitti, Nofa; Banase, Yustina; Imron, Ali; Kumilah, Kumilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of discussion and Snowball trowing learning methods on increasing motivation to learn social studies. This research uses a classroom action method with two action cycles. Each cycle includes planning activities, implementing actions, observing and reflecting. The significant increase in motivational conditions for learning social studies is correlated with students' enthusiastic attitudes towards the application of discussion and snowball trowing methods in social studies learning. The motivation to learn social studies for Class VIII students at SMP Negeri 42 Surabaya can be increased through discussion and snowball trowing methods.